2016
DOI: 10.1111/mec.13711
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to warmer climates by parallel functional evolution of CBF genes in Arabidopsis thaliana

Abstract: The evolutionary processes and genetics underlying local adaptation at a specieswide level are largely unknown. Recent work has indicated that a frameshift mutation in a member of a family of transcription factors, C-repeat binding factors or CBFs, underlies local adaptation and freezing tolerance divergence between two European populations of Arabidopsis thaliana. To ask whether the specieswide evolution of CBF genes in Arabidopsis is consistent with local adaptation, we surveyed CBF variation from 477 wild a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 57 publications
2
46
0
Order By: Relevance
“…To further address the generality of this finding , Monroe et al. () surveyed CBF variation from 477 wild accessions collected across the species' range. They found that CBF sequence variation is strongly associated with winter temperature variables, thus suggesting that the disruption of CBF gene function is adaptive only in warm climate.…”
Section: Evidence For Polygenic Selection and Gene Interactions From mentioning
confidence: 99%
“…To further address the generality of this finding , Monroe et al. () surveyed CBF variation from 477 wild accessions collected across the species' range. They found that CBF sequence variation is strongly associated with winter temperature variables, thus suggesting that the disruption of CBF gene function is adaptive only in warm climate.…”
Section: Evidence For Polygenic Selection and Gene Interactions From mentioning
confidence: 99%
“…CBF3/DREB1A and CBF/DREB1B are induced at the same time and earlier than CBF2/DREB1C (Medina et al 2011). More recently Monroe et al (2016) screened 477 wild accession from Arabidopsis for the variation in CBF genes; they found that CBF sequences variation is strongly associated with winter temperatures. The types that come from warmer winters showed significant access to the CBF polymorphisms.…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…In humans, 19 UGT isoforms have been identified, and these UGTs have been classified into two families (UGT1 and UGT2) based on their sequence identity [9]. In the model plant, Arabidopsis thaliana , more than 120 UGTs encoding genes have been identified, with five UGTs found to be correlated with flavonoid biosynthetic [10–12]. A total of 253 UGTs were found in Panax ginseng transcriptome, and recent works have confirmed the function of UGTs in ginsenoside biosynthesis [13–15].…”
Section: Introductionmentioning
confidence: 99%